Relationships between enabling services use and access to care among adults with cardiometabolic risk factors: findings from the 2014 National Health Center Patient Survey - G. Sofia Martinez; Kellee White; Dahai Yue; Luisa Franzini; Craig S. Fryer; Ninet Sinaii; Dylan H. Roby (BMC, 2022)
Abstract Background Community health centers (CHCs) provide comprehensive primary and preventive care to medically underserved, low-income, and racially/ethnically diverse populations. CHCs also offer enabling services, non-clinical assistance to reduce barriers to healthcare due to unmet social and material needs, to improve access to healthcare and reduce health disparities. For patients with modifiable cardiometabolic risk factors, including obesity, hypertension, and diabetes, enabling services may provide additional support to improve disease management. However, little is known about the relationship between enabling services and healthcare accessibility and utilization among patients with cardiometabolic risk factors. Methods This study uses data from the 2014 Health Center Patient Survey to examine the relationship between enabling services use and delayed/foregone care, routine check-ups, and emergency room visits, among adult community health center patients in the United States with cardiometabolic risk factors (N = 2358). Outcomes of enabling services users were compared to nonusers using doubly robust propensity score matching methods and generalized linear regression models. Results Overall, enabling service users were 15.4 percentage points less likely to report delayed/foregone care and 29.4 percentage points more likely to report routine check-ups than nonusers. Enabling service users who lived in urban areas, younger and middle-aged adults, and those with two cardiometabolic risk factors were also less likely to report delayed/foregone care and/or more likely to report routine check-ups in comparison with nonusers. However, among adults with three or more cardiometabolic risk factors, enabling services use was associated with a 41.3 percentage point increase in emergency room visits and a 7.6 percentage point decrease in routine check-ups. Conclusions The findings highlight the value in utilizing enabling services to improve timeliness and receipt of care among CHC patients with heightened cardiometabolic risk. There is a need for targeting high-risk populations with additional enabling services to support management of multiple chronic conditions.